EXPLORING THE CREDIBILITY OF DIGITAL MEDIA CONTENT DURING COVID-19: A STUDY FROM THE PERSPECTIVE OF COVID-19 AFFECTED PATIENTS - Mathur, Pallavi; Mukherjee, Tanushri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The world has been innumerably affected by various kinds of health problems and diseases. However, none of them have been so dreadful and life threatening like Covid-19. The Novel coronavirus is a respiratory syndrome that affects the respiratory functions of a human being and the most surprising element associated with it is its ever-changing form and variant posing new challenges to the health fraternity members and scientists. A major question which arises is that with the sudden outbreak of the disease, how can the general public be informed about the various facts related to the virus and the medical facilities available for its treatment and cure. General masses in such times need reliable and trustworthy information about the pandemic as the sudden onslaught of the virus shook the entire world and brought everybody’s life to a standstill, which nobody had ever dreamt of.